Riffat Hassan dan Wacana Baru Penafsiran - Afifah Bidayah (Kalimah: Jurnal Studi Agama dan Pemikiran Islam, 2013)
In the discourse of women’s liberation was hailed by adherents of gender equality, Hermeneutics has a significant role. It can be seen clearly by considering the function Hermeneutics deemed capable of reconstructing the verses (nass) which considered Misogyny or gender biased. One of the figures who hard enough to practice Hermeneutics as one means to ‘rediscover’ the rights of women in the texts, is Riffat Hassan. Riffat, with her efforts to try to re-interpret the meanings in the Qur’an related to the gender discourse. For Riffat, patriarchal culture that deeply ingrained was implications of hegemonic texts understanding. Women, for Riffat have rights and obligations in the portion of the ‘same’ in quantity without having to think about the logical consequences are present therefrom.